2016
DOI: 10.1021/acs.jafc.5b05378
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Herbicidal Activity, and QSAR of Novel N-Benzothiazolyl- pyrimidine-2,4-diones as Protoporphyrinogen Oxidase Inhibitors

Abstract: Protoporphyrinogen oxidase (PPO, E.C. 1.3.3.4) is known as a key action target for several structurally diverse herbicides. As a continuation of our research work on the development of new PPO-inhibiting herbicides, a series of novel 3-(2'-halo-5'-substituted-benzothiazol-1'-yl)-1-methyl-6-(trifluoromethyl)pyrimidine-2,4-diones 9 were designed and synthesized. The bioassay results indicated that a number of the newly synthesized compounds exhibited higher inhibition activity against tobacco PPO (mtPPO) than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 45 publications
(51 reference statements)
2
76
0
Order By: Relevance
“…Compound 17 was treated with methyl chloroformate to give compound 18 in 86% isolated yield with >98% purity (HPLC). Compound 18 was reacted with ethyl 3‐amino‐4,4,4‐trifluorobut‐2‐enoate ( 2 ) to form the uracil ring to give compound 19 in 78% isolated yield with >99% purity (HPLC) . At the last step, compound 19 was methylated in a two‐phase reaction system to give the final product saflufenacil ( 1 ) in around 86% yield and 98.7% purity (HPLC).…”
Section: Resultsmentioning
confidence: 99%
“…Compound 17 was treated with methyl chloroformate to give compound 18 in 86% isolated yield with >98% purity (HPLC). Compound 18 was reacted with ethyl 3‐amino‐4,4,4‐trifluorobut‐2‐enoate ( 2 ) to form the uracil ring to give compound 19 in 78% isolated yield with >99% purity (HPLC) . At the last step, compound 19 was methylated in a two‐phase reaction system to give the final product saflufenacil ( 1 ) in around 86% yield and 98.7% purity (HPLC).…”
Section: Resultsmentioning
confidence: 99%
“…Based on molecule superimposition or protein crystallography, 3D-QSAR has evolved as a powerful tool in-depth analysis on the correlation between activities and interaction fields, and has been widely used in ligand-based drug design strategies (Beca et al, 2011;Chen, Zhu, Jiang, Liu, & Yang, 2008;Li, Zhang, Li, Zhang, & Chen, 2011;Sashidhara et al, 2015;Yang, Liu, & Yang, 1999;Zuo et al, 2016). Despite numerous 3D-QSAR studies on PDE4 inhibitors with deferent structure types having been published (Gratteri, Bonaccini The actual IC 50 against human PDE4 catalytic domains (PDE4CAT) were obtained from our reported references (Zhou et al, 2015 Marella et al, 2013;Xiong, Lu, Li, Yang, & Zhan, 2006;Zheng et al, 2008), the application of 3D-QSAR study in the design and development of new PDE4 inhibitors is still scarce.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative structure-activity relationship (QSAR) is widely used studying the immune recognition of diffferent classes of toxic food contaminants, veterinary drugs, including pesticides, etc [11][12][13][14]. The work by Yuan and co-authors reported about an immunoassay analysis of triazines, yet on a small set of 11 compounds [9].…”
Section: Introductionmentioning
confidence: 99%